News frames for the phenomenon of terrorism in international satellite channels directed in Arabic An analytical study of the main news bulletins in the Russian channel today 1/2/31/5/2018 - Al – Rubaie, Walaa Mohammed Ali; Khazaal, Abdel-Nabi (ALBAHITH ALALAMI, 2019)
International satellite channels in Arabic are targeted to the region with their news bulletins and their innovative programs, attracting the interest of the Arab viewers in their news articles and programs with new ideas and methods as well as high technology in the production and synthesis of videos. Therefore, they work on framing the above, And the media policy that governs, so focused the problem of the study to try to answer the question of the President is how to frame the international satellite channels in Arabic to the phenomenon of terrorism? What are the aspects that are working to highlight and aspects that try to hide? The study adopted the survey methodology for the main news bulletins in the Russian channel today for the period from 1 / 2-31 / 5/2018. The sample was extracted in a random random way. The number of bulletins (33) ), Which has been analyzed and highlights the findings of the study is that the international satellite channels focus on criminalizing the perpetrators of terrorist acts and work to highlight these acts and expose methods as trying to identify terrorism and its support to the supporters